2015
DOI: 10.1515/pjvs-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Large granular lymphoma in six cats

Abstract: Large granular lymphomas (LGLs) comprise a specific group of lymphomas regardless of classification scheme. An LGL consists of cells that show less or more mature morphology, but typically neoplastic cells possess cytoplasmic azurophilic granules clearly visible during cytological examination. The aim of the present study was to present clinical and cytological data on large granular lymphomas in cats and to analyses the therapeutic responses in treated cases. During the period from 2012 to 2014 six cats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 11 publications
0
19
1
Order By: Relevance
“…There is also a dichotomy in cases of feline LSA, with potentially greater than half of cats lacking significant response to chemotherapy and only a small subset of cats entering a durable clinical remission. Cats that are nonresponsive to chemotherapy have short MST ranging from 27 to 73 days, which is less than or statistically equal to the MST in this study.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…There is also a dichotomy in cases of feline LSA, with potentially greater than half of cats lacking significant response to chemotherapy and only a small subset of cats entering a durable clinical remission. Cats that are nonresponsive to chemotherapy have short MST ranging from 27 to 73 days, which is less than or statistically equal to the MST in this study.…”
Section: Discussioncontrasting
confidence: 82%
“…Similarly to previous reports, immunophenotype and/or morphological phenotype was not found to be predictive of survival. Although large granular LSA historically has been noted to have a poor long‐term prognosis, with some reported MST less than two months, this group had the longest MST in the study reported here . This subtype is often noted to be particularly aggressive, usually with advanced disease at diagnosis, but only 50% of the LGL‐type cats in this study had confirmed involvement of their LSA in local lymph nodes.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations